Strategies to Reduce Young Adult Pregnancy in Selected Rural Villages in Mthatha, South Africa - Kundlwana, Babalo; Asoba , Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
Background: Pregnancy among young adults is still a major public health issue that affects people individually, in families, and communities. It is driven by a complex interplay of socioeconomic, educational, and psychological factors that necessitate in-depth, context-specific investigation to inform targeted interventions. Aim: This article aims to explore the perspectives of young mothers in selected rural villages of Mthatha on strategies to reduce young adult pregnancy and to examine their views on the influence of the Child Support Grant on pregnancy decisions and maternal experiences. Setting: The study was conducted in rural villages surrounding Mthatha, a region characterised by high unemployment, poverty, and limited access to health and educational resources. Methods: A qualitative research design was employed. Data were collected through in-depth, semi-structured interviews with young women who had experienced pregnancy. Participants were recruited using a snowball sampling strategy. Thematic analysis was used to interpret the data, focusing on recurring patterns and significant themes. Results: The need for early and thorough sexual education, better access to contraception, and parental involvement in sex education are just a few of the methods that participants indicated as being necessary to prevent young adult pregnancy. The importance of community support, youth engagement initiatives, and awareness campaigns in fostering informed decision-making and postponing early sexual activity was also stressed. Furthermore, the results showed that many participants did not consider the Child Support Grant to be a driving force behind pregnancy, pointing out that it was insufficient to cover all the expenses associated with raising a child. Although a small percentage of respondents agreed that extreme poverty might affect some young women’s choices, more general issues like peer pressure, emotional fragility, and a lack of sexual health education were more frequently mentioned as causes of early pregnancy. Conclusion: According to the study’s findings, preventing young adult pregnancy necessitates a multifaceted strategy that incorporates socioemotional support, accessible contraceptive options, parental and community involvement, and thorough sexual education. Early pregnancy is mostly caused by educational, social, and psychological vulnerabilities rather than the Child Support Grant, even though it offers young mothers crucial support. Contribution: This study provides context-specific information about young mothers’ perspectives and reproductive experiences in rural Mthatha. It advances an ecohumanist understanding of how familial dynamics, emotional needs, and institutional injustices interact to influence reproductive decision-making by elevating the voices of young people. The results lay the groundwork for inclusive policy frameworks and community-based initiatives that support young women’s dignity, equity, and informed agency.